SINERGI PENDIDIKAN ANTI KORUPSI DAN NILAI ANTI KORUPSI DALAM MENANGKAL KORUPSI DI INDONESIA - Vina Imelda Putri (Universitas Pendidikan Ganesha, 2022)
Corruption is not a taboo in society, from time to time, corruption has become a problem that does not go away, corruption has an impact on the loss of the state and society so that they cannot experience prosperity and well-being in their lives. Literally, a criminal act of corruption that is deliberately committed to gain profit where the act is contrary to the responsibilities, authorities, rights or position of someone who is in charge officially. The purpose of writing this article is to analyze and describe related problems to the efforts of all elements of society in eliminating the